Identification of an Electric Resistance Furnace - Chook, Kam Chee; Tan, Ai Hui (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2007)
In this paper, the identification of an electric resistance furnace is described. Physical modeling is applied to obtain a mathematical description that captures the static and dynamic behavior of the furnace. Experimental data are collected and used for estimating the parameters of the furnace, which is found to be a dominantly first-order system. First-order linear, bilinear, and direction-dependent models are employed to describe the characteristics of the furnace. A comparison between the quality of these models is made. It was found that the bilinear model provides the best fitting among the three models considered for this particular application.